Knowledge on protein energy malnutrition (PEM) among the female community health volunteers (FCHVs) in Salyan district, Nepal. - Oli, Chitra Bahadur (2009)
ABSTRACT: Good nutrition is essential for survival, physical growth, mental development, performance, productivity, health and well-being across the entire life-span, 49% of the 10.4 million deaths associated with PEM are occurring in children younger than 5 years in developing countries,6 whereas 21% LBW, 48% moderate and 13% severe underweight, 10% wasting and 51% stunting under five children are in Nepal.28 FCHVs are unquestionably the backbone of health activities at the grassroots level, no proper study had been done regarding knowledge on PEM among FCHVs. To explore the knowledge on PEM descriptive cross-sectional study was conducted among 135 FCHVs by face to face interview using pretested semi structured questionnaire and two FGD among 16 participants by using FGD guideline and data were analyzed by using SPSS (version 16).Among total 135 respondents, one third of the respondents were of 19-28 years age group. 100% of the respondents were Hindu and 53.3% of the respondents were Kshetri. Regarding education, 30.4% had primary education and 36.3% of the respondents had working experience less than 5 years. Half (50%) of the respondents had nuclear family. Majority (57.8%) had family income less than 6000 NRs. Moreover, 83.7% were housewives and 8.1% were doing further study as their extra personal works. More than one third (33.3%) were living 1-3 Km distance far from health institution. 24.4% FCHVs were never supervised. Majority (78.52%) FCHVs were rewarded. Majority (54.1%) were getting support from mothers group. Similarly, Majority (72.6%) of the respondents got information regarding PEM from training and meeting. 54.8% FCHVs used poster/pamphlets and radio to get the information. Association between education of the respondents, working experience and types of family with level of knowledge was found statistically significant p = 0.016, p = 0.046 and p=0.044 respectively.